2001
DOI: 10.1046/j.1365-2036.2001.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal anti‐inflammatory activity of morin on chronic experimental colitis in the rat

Abstract: In¯ammatory bowel disease is a chronic disease of the digestive tract, and usually refers to two related conditions, namely ulcerative colitis and Crohn's disease. The aetiology of in¯ammatory bowel disease remains unknown, although it is believed that an alteration in the intestinal immune system contributes to the in¯ammation that occurs. As in other in¯am-matory processes, in¯ammatory bowel disease is characterized by an up-regulation in the synthesis and release of different pro-in¯ammatory mediators, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 49 publications
3
83
0
1
Order By: Relevance
“…Being yellow crystalline when extracted and purified, morin hydrate has exhibited a wide range of beneficial pharmacological effects, including anti‐cancer 10 and anti‐inflammatory activities 11, xanthine oxidase inhibitor property 12, preventing oxidation of low‐density lipoprotein 13, free radical scavenging activity 14 which in turn prevented DNA damage 15. However, to date, its function in NSC growth and differentiation, as well as in preventing neuronal hearing loss, has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Being yellow crystalline when extracted and purified, morin hydrate has exhibited a wide range of beneficial pharmacological effects, including anti‐cancer 10 and anti‐inflammatory activities 11, xanthine oxidase inhibitor property 12, preventing oxidation of low‐density lipoprotein 13, free radical scavenging activity 14 which in turn prevented DNA damage 15. However, to date, its function in NSC growth and differentiation, as well as in preventing neuronal hearing loss, has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the constituents of RM possess antiinflammatory and antioxidant parmacologic activities. [3][4][5] We suggest that some of these components may have a synergistic effect on CIA. Further research is needed to determine which fractional extraction of ERM is most effective in CIA mice.…”
Section: Discussionmentioning
confidence: 99%
“…Morin has excellent antioxidant and antiinflammatory activities and suppresses inflammation induced by macrophages. [3][4][5] MR has immune-adjusting, antihypertensive, antibacterial, analgesic, and antiinflammatory effects and is frequently used to treat hypertension, RA, and diabetes. It promotes the conversion of lymphocytes associated with depressed systemic immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are excellent candidates because of their anti-inflammatory properties and their low toxicity. Several flavonoids have been shown to exert intestinal anti-inflammatory activity in vivo, including (mg/kg) quercitrin 1-5 (1) , rutin 10-25 (2) , morin 25 (3,4) , hesperidin and diosmin 10-25 (5) . However, the mechanism of action is unclear.…”
mentioning
confidence: 99%
“…, rutin 10-25 (2) , morin 25 (3,4) , hesperidin and diosmin 10-25 (5) . However, the mechanism of action is unclear.…”
mentioning
confidence: 99%